The Obsessive Compulsive and Related Disorders with its Homoeopathic Management (Homoeopathy for All, 2024)
Obsessive-compulsive disorder  (OCD) is a chronic mental illness  in which a person experiences ir rational, recurrent thoughts (obses sions), engages in irrational, re petitive activities (compulsions),  or both. Homeopathy is one of the  most popular supplemental medi cal practices. In homoeopathy, the  principle of individualization serves  as the foundation for remedy selec tion. Homoeopathy is a holistic sci ence that takes into account even  the smallest characteristics of the  patient, unlike modern conventional  medicine, where the doctor spends  relatively little time with the patient.  This article discusses the role of ho meopathic medicines for obsessive compulsive and related disorders.
Keywords: Obsessive compulsive disorder; Homeopathy; Obsessive Compulsive and Related Disorders; DSM-5; Mental health; Psychiatry